1998
DOI: 10.1051/rnd:19980109
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different planes of energy supply prior to the breeding season on blood metabolites in female mink (Mustela vison)

Abstract: -Metabolic blood profiles were studied in a total of 30 female mink (Mustela vison) at different planes of nutrition prior to the breeding season in a control (CON; n = 10), a flushed (FLUSH; n = 10) and a negative energy balance group (NEG; n = 10). The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
2
8
0
1
Order By: Relevance
“…Period effects were significant for thyroid hormones and IGF-1 and with insulin there was only a tendency for them; concentrations decreased during restriction and increased during refeeding. These results were in good agreement with [17,18].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Period effects were significant for thyroid hormones and IGF-1 and with insulin there was only a tendency for them; concentrations decreased during restriction and increased during refeeding. These results were in good agreement with [17,18].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, limited data have indicated that flush feeding may result in a more synchronised LH release and in more distinct peaks [42], but here, sampling frequency was too limited to allow for an un-ambiguous description of the LH release pattern. Also metabolic traits such as plasma concentrations of insulin and thyroid hormones [17] as well as IGF-1 [18] have been shown to be affected by energy supply prior to the breeding season, but the response has not been related to reproductive endocrinology.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that insulin changes rapidly in mink in response to changes in energy supply (Fink et al 1998;Tauson et al 2000), which was confirmed here and fits the concept of insulin as regulator of energy-supply-induced changes in leptin secretion (Havel, 2000). However, food restriction may cause an increased sympathetic activity to the white adipose tissue (Migliorini et al 1997), and this regulation mediated via catecholamines and b-agonists seems to be more pronounced than other regulatory factors , so it cannot be excluded that this mechanism was the main cause of the decrease in plasma leptin during food restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma concentrations of insulin were determined by radioimmunoassay (Pharmacia insulin radioimmunoassay; Kabi-Pharmacia, Uppsala, Sweden) previously validated for mink plasma (Fink et al 1998). The within-assay CV estimated from the precision profile was , 15 % for concentrations between 3 and 240 mU/ml.…”
Section: Methodsmentioning
confidence: 99%
“…De esta forma, dietas altas en fibra aumentan la producción lechera (Nizza et al, 1997;Pascual et al, 2002) y disminuyen la movilización de grasas en la hembra (Xiccato et al, 1999), sin afectar al intervalo entre partos ni a la vida útil de la hembra (Pascual et al, 2002). Dado que en otras especies, aumentar la energía obtenida con la dieta algunos días antes del coito da buen resultado (Ebling y Foster, 1991;Fink et al, 1998;Khireddine et al, 1998), se han realizado algunos estudios para comprobar si este efecto positivo ocurría también en conejos, sin obtener resultados concluyentes. Mientras que el aumento de energía en la dieta 10 días antes del coito en hembras multíparas lactantes aumentó su fertilidad (Fortun-Lamothe, 1998), si este aumento se realizaba cuatro días antes, no se observaba ningún efecto (Maertens, 1998).…”
Section: )unclassified